Konservasi Lingkungan dan Efisiensi Energi di Lingkungan Kampus Universitas Warmadewa: Sebuah Kajian Komprehensif Menuju Kampus Berkelanjutan - I Wayan Werasmana Sancaya; Putu Ayu Sita Laksmi; I Made Yogiarta (Lembaga Penelitian, Universitas Warmadewa, 2025)
Commitment to sustainability has become an important parameter in the management of higher education institutions in the 21st century. Warmadewa University, as one of the leading higher education institutions in Bali, has a moral and academic responsibility to lead in the application of sustainable principles, particularly in environmental conservation and energy efficiency. This research aims to comprehensively examine the practices, challenges, and opportunities in implementing environmental conservation and energy efficiency within the Warmadewa University campus environment. The research method used is qualitative descriptive with a case study approach, involving field observations, in-depth interviews with stakeholders (lecturers, staff, students, and facility managers), and analysis of university policy documents. The results show that Warmadewa University has taken several positive initiatives, such as the installation of rooftop solar panels, limited waste management programs, and campus greening. However, the findings also reveal that these efforts are still fragmented and not yet integrated into a holistic sustainable campus policy framework. The main challenges include budget limitations, uneven awareness within the campus community, and the lack of a robust monitoring and evaluation system. The discussion in this article emphasizes the importance of an integrated approach that combines policy, technological, financial, and cultural aspects. This article concludes by recommending concrete strategies, such as the development of a Sustainable Campus Master Plan, strengthening the energy management system, optimizing water and waste management, and integrating sustainability education into the curriculum to create a sustainable conservation culture at Warmadewa University